The Rate of Discontinuing Ready-to-Use Multi-Chamber Bag Parenteral Nutrition Secondary to High Serum Electrolyte Levels. (June 2023) - Hakeam, Hakeam; Alsemari, Muhannad; Mohamed, Gamal; Alshahrani, Asma; Islami, Muna
Background: Multi-chamber bag with electrolytes (MCB-E) parenteral nutrition (PN) formulations are gaining acceptance for nutritional support for safety and economic advantages. However, their use is hampered by serum electrolyte abnormalities. No data exist regarding MCB-E PN interruption due to high serum electrolyte levels. We assessed the rate of MCB-E PN discontinuation in surgical patients secondary to persistently high serum electrolyte levels.Methods: This prospective, cohort study included surgical patients (aged ≥18 years) who received MCB-E PN at King Faisal Specialist Hospital and Research Centre-Riyadh, from February 28, 2020, until August 30, 2021. Patients were followed for 30-day for the discontinuation of MCB-E PN secondary to persistent hyperphosphatemia, hyperkalemia, hypermagnesemia, or hypernatremia for two consecutive days. The association of discontinuing MCB-E PN with various factors was assessed using univariable and multivariable Poisson regression analysis.Results: Seventy-two patients were enrolled in the study, 55 (76.4%) completed MCB-E PN, whereas 17 (23.6%) patients discontinued MCB-E PN due to a persistent hyperphosphatemia (n = 13, 18%) and persistent hyperkalemia (n = 4, 5.5%). Hyperphosphatemia and hyperkalemia were observed at a median of 9 (IQR 6-15) days and 9.5 (IQR 7-12) days of MCB-E PN support, respectively. According to adjusted multivariable analysis, developing an episode of hyperphosphatemia or hyperkalemia was associated with MCB-E PN discontinuation (RR 6.62, 1.95-22.49; P = .002) and (RR 4.73, 1.30-17.24; P = .018), respectively.Conclusion: In surgical patients receiving short-term MCB-E PN, developing hyperphosphatemia was the most frequent high electrolyte abnormality assocaited with MCB-E PN discontinuation, followed by hyperkalemia.